Cubic Calculus - Fidan, Saner (Eastern Mediterranean University)
ABSTRACT: In the study called non-Newtonian Calculus, Grossman and Katz introduced a new type of calculus that includes branches such as geometric and bi-geometric calculus. The aim of this thesis is to examine the basic features of the geometric and bigeometric calculus. This thesis is divided into five parts. In the first part, the literature on non-Newtonian calculus is summarized. In the second part, a sub-branch of non-Newtonian calculus called geometric arithmetic is introduced, along with the properties of geometric real numbers which is called 𝛼-arithmetic. In the third part, the applications of the 𝛼- arithmetic of non-Newtonian calculus is studied. In chapter four the arithmetic, differentiation and integration are applied to a specific example which is hyperbolic tangent. In chapter 5 the application of arithmetic to the cubic calculi is given and according to this geometric and bi-geometric differentiation and integrations are defined. Apart from this some other concepts are given such as absolute value, commutativity, associativity and distributivity properties and q-limit. In conclusion part a discussion about quadratic Calculi is given. Keywords: Non-Newtonian Calculus, 𝛼-Arithmetic, Geometric Calculus, BiGeometric Calculus, Cubic Calculi and Quadratic Calculi.

ÖZ: Grossman ve Katz, Geometrik ve Bi-Geometrik kalkülüs gibi alt dalları içeren yeni bir kalkülüs türü olan Non-Newtonian Kalkülüsün tanıtımını yaptılar. Bu tezde, Geometrik ve İki-Geometrik kalkülüsün temel özelliklerini inceleme amacı taşımaktadır. Bu tez, beş bölümden oluşur. Birinci bölümde, non-Newtonian kalkülüsün tarihçesi ve bilgileri özetlenir. İkinci bölümde, non-Newtonian kalkülüsün bir alt dalı olan Geometrik Aritmetik tanıtılır ve α-aritmetiği olarak bilinen Geometrik gerçek sayıların özellikleri verilir. Üçüncü bölümde, non-Newtonian kalkülüsün α-aritmetiğinin uygulamaları incelenir. Dördüncü bölümde aritmetik, türev alma ve tümevarım işlemleri, hiperbolik tanjant örneği üzerinde uygulanır. Beşinci bölümde aritmetik, kübik kalkülüslere uygulanır ve bu doğrultuda geometrik ve iki-geometrik türev alma ve tümevarım işlemleri tanımlanır. Ayrıca, mutlak değer, komütatiflik, örtüklük ve dağılma özellikleri ve kübik-limit gibi diğer kavramlar verilir. Sonuç bölümünde Kuadratik Kalkülüs ile ilgili tartışma yapılır. Anahtar kelimeler: Non-Newtonian Kalkülüs, α-Aritmetik, Geometrik Kalkülüs, BiGeometrik Kalkülüs, Kübik Kalkülüs ve Kuadratik Kalkülüs
Master of Science in Mathematics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2023. Supervisor: Prof. Dr. Aghamirza Bashirov
Keywords: Thesis Tez; Mathematics Department; Calculus; Non-Newtonian Calculus; a-arithmetic; Geometric Calculus; Bi-Geometric Calculus; Cubic Calculi and Quadratic Calculi